Food preferences before and during treatment for a pediatric feeding disorder. Issue 2 (27th August 2019) - Zeleny, Jason R.; Volkert, Valerie M.; Ibañez, Vivian F.; Crowley, Jaime G.; Kirkwood, Caitlin A.; Piazza, Cathleen C.
Abstract : Little is known about the food preferences of children with a feeding disorder and medical diagnoses. Therefore, we conducted repeated paired‐stimulus‐preference assessments with foods to which we either exposed or did not expose 3 children with a feeding disorder and medical diagnoses during clinical treatment. Responding was relatively equivalent for exposure and nonexposure foods throughout the preference assessments, suggesting that preferences for foods did not change due to exposure during treatment.